PayPal Hacks - Burchell, Dave (O'Reilly, 2011)
Learn how to make the most of PayPal to get the most out of your online business or transactions. From how to take steps to protect yourself while buying and selling on eBay to using PayPal on your own site to handle subscriptions, affiliations, and donations, PayPal Hacks provides the tools and details necessary to make PayPal more profitable, more flexible, and more convenient.